L-asparaginase-based regimens followed by allogeneic hematopoietic stem cell transplantation improve outcomes in aggressive natural killer cell leukemia. Issue 1 (December 2016) - Jung, Ki; Cho, Su-Hee; Kim, Seok; Ko, Young; Kang, Eun-Suk; Kim, Won
Abstract Aggressive nature killer cell leukemia (ANKL) is a mature NK-T cell lymphoma with worse prognosis, but optimal treatment is unclear. Therefore, we analyzed the efficacy ofl -asparaginase-based regimens for ANKL patients. Twenty-one patients who received dexamethasone, methotrexate, ifosfamide, l -asparaginase, and etoposide (SMILE) or etoposide, ifosfamide, dexamethasone, andl -asparaginase (VIDL) chemotherapy at Samsung Medical Center were selected. The overall response rate for all patients was 33 % (7/21); 38 % (5/13) in SMILE and 40 % (2/5) in VIDL, respectively. The median progression-free survival was 3.9 months (95 % CI 0.0–8.1 months) and median overall survival was 7.0 months (95 % CI 2.3–11.7 months). Treatment response (P  = 0.001), hematopoietic stem cell transplantation (HSCT) (P  = 0.007) and negative conversion of Epstein-Barr virus (EBV) DNA titer after treatment (P  = 0.004) were significantly associated with survival. Thus, l -asparaginase-based regimens followed by allogeneic HSCT seem to improve the outcome for ANKL patients.